Metode Field Trip dalam Pembelajaran Menulis Deskripsi Berbasis Kearifan Lokal: Penelitian - Agung Nasrulloh Saputro (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to describe and explain the application of learning to write descriptive essays based on local wisdom using the field trip method for class V students at SDN 2 Pupus, Ngebel District, Ponorogo Regency, Academic Year 2024/2025. This research uses a qualitative descriptive method. Data collection techniques in this research are observation, interviews and documentation. The technique used to analyze data in this research is the interactive model from Miles and Huberman. The results of this research are the implementation of learning to write descriptive essays based on local wisdom using the field trip method for class V students at SDN 2 Pupus, Ngebel District, Ponorogo Regency, Academic Year 2024/2025, running as planned.